If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(2n + 6) = 4(n + -3) Reorder the terms: 0.5(6 + 2n) = 4(n + -3) (6 * 0.5 + 2n * 0.5) = 4(n + -3) (3 + 1n) = 4(n + -3) Reorder the terms: 3 + 1n = 4(-3 + n) 3 + 1n = (-3 * 4 + n * 4) 3 + 1n = (-12 + 4n) Solving 3 + 1n = -12 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 3 + 1n + -4n = -12 + 4n + -4n Combine like terms: 1n + -4n = -3n 3 + -3n = -12 + 4n + -4n Combine like terms: 4n + -4n = 0 3 + -3n = -12 + 0 3 + -3n = -12 Add '-3' to each side of the equation. 3 + -3 + -3n = -12 + -3 Combine like terms: 3 + -3 = 0 0 + -3n = -12 + -3 -3n = -12 + -3 Combine like terms: -12 + -3 = -15 -3n = -15 Divide each side by '-3'. n = 5 Simplifying n = 5
| 48r=12 | | 2x-3=6x-17 | | 0.25d=130 | | -8+4k=16 | | -42=-6b | | 5x^2-20x=10 | | 2(3a+12)=3(4a+2) | | 3c=-18 | | y^2+18y+32=226 | | 6x+5=2x-11 | | t-19=-2(t+5) | | z-6=-10 | | v^2-20v+19=0 | | p-22=3(2p-4) | | 6x-5=2x-11 | | -4+a=15 | | 6x+7y=13 | | 12x+5=8x+13 | | 2y-6=9-3y | | w^2+6w=-3 | | log(y)=1.6 | | 4=m+19 | | 9d-1=2d+20 | | x^3+6x+9=49 | | 2x^3+12x^2+22x+12=0 | | -5z+4+6z=40 | | 3x+5=2x+4 | | 47=(7z-3)-(4z-11) | | -6x-167=9x+88 | | 6u=96 | | -6x-167=88 | | 2x^2+8x+31=0 |